Latin American decolonial feminisms: theoretical perspectives and challenges - Bárbara Martínez-Cairo; Emanuela Buscemi (Les Cahiers ALHIM)
The purpose of the present investigation is to critically examine decolonial feminisms’ epistemologies and practices in order to open up the debate on decoloniality and gender in the South of the world, in particular focusing on the Latin American context. Employing an analysis of the historical developments of white hegemonic feminism, the article offers a reflection on its failure to universalize women’s struggles, presenting a discursive examination of the primary critiques generated in the Souths of the world, including the Souths of the North. Decolonial feminisms are, thus, investigated as a form of theoretical and praxical response to the aforementioned critiques, generated in relation to the discursive and actual perpetuation of the material and symbolic legacies of colonialism. It is here argued that decolonial feminisms employ this alternative perspective as a de facto standpoint, by rooting their principles in anti-racist, anti-capitalist and anti-imperialist narratives, and with some strong established goals, such as social and environmental justice, the rights of indigenous people, and the decolonization of knowledge.